KETERDAPATAN DAN GENESA CEBAKAN BIJIH BESI DAERAH KAPAYANG, KABUPATEN TANAH BUMBU, KALIMANTAN SELATAN: THE OCCURENCES AND GENETIC OF IRON ORE DEPOSITS IN KAPAYANG, TANAH BUMBU REGENCY, SOUTH KALIMANTAN - Pardiarto, Bambang; Bambang; Wahyu Widodo (Buletin Sumber Daya Geologi, 2024)
The occurences of iron mineralisation in upper part of Kusan River, Kapayang, Regency of Tanah Bumbu are still indicative and required more research to reveal the characteristic and potency of iron ore deposits. The research was conducted with reconnaissance survey using methode of geological mapping, sampling of rock, iron ore, lateritic soil, and panning concentrate of crushed ore material. The laboratory analyses involve petrographic, mineragraphic, grain mineralogy and geochemical assay. Iron ore in the research area consist of two deposit type are primary iron and lateritic iron. The genetic is related to procces of magmatism, metamorphism/metasomatic and hydrothermal. The primary iron ore mineral in altered dunite and gneiss-schist rocks are dominated by magnetite and hematite, some chromite and garnet. While in lateritic iron as resulted from weathering of pyroxenite-peridotite rock consist of hematite magnetite and goetit. Potency of exploration target of lateritic iron is 158,264 wmt and the grade of Fetot ranging from 49.45 to 54.89%. Grid soil geochemical exploration is suggested for follow up work using hand auger to collect soil sample in laterisation zone to obtain more optimize reource potency.